Perencanaan, Penganggaran dan Capaian Target Program Wajib Belajar 12 Tahun : Kasus di Kabupaten Bogor dan Kabupaten Bandung - Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.09.TAHUN 2018, 2018)
Increasing the status of the nine-year compulsory education program into a twelve-year compulsory education program is a challenge for local governments to make it happen because of the fact that occurred in the field that the education office of Bogor Regency and Bandung District Education Office has not been able to complete the nine-year compulsory education, whereas the program is targeted to be completed in 2008 ago. This proves that the government's performance in realizing the compulsory education program is slow. To realize the twelve-year compulsory education mission required consistency in the preparation of planning and budgeting. Problem that occurs is planning and budgeting in education offices Bogor and Bandung regency is still not consistent because of the difference between programs and budgets between documents with each other. These inconsistencies affect the achievement of the twelve-year compulsory education program has not reached a predetermined target.